1992
DOI: 10.1002/ajmg.1320440309
|View full text |Cite
|
Sign up to set email alerts
|

Bannayan‐Riley‐Ruvalcaba syndrome

Abstract: Here we report on 12 affected members of a family with Bannayan-Riley-Ruvalcaba syndrome. We present clinical evidence of overlap between Bannayan-Zonana syndrome. Riley-Smith syndrome, and Ruvalcaba-Myhre syndrome in this autosomal dominantly inherited condition. We expand the phenotypic spectrum to include Hashimoto thyroiditis, which occurred in 7 of our cases. Finally, we discuss the relationship between the syndrome and juvenile polyposis of infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
171
0
4

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(176 citation statements)
references
References 68 publications
1
171
0
4
Order By: Relevance
“…Both patients came to our attention for clinical features suggestive of BRRS such as macrocephaly, developmental delay, and subcutaneous lipomatosis. Macrocephaly with normal ventricular size has been the most consistent finding in BRRS in several reviews [MorettiFerreira et al, 1989;Gorlin et al, 1992]. It is noteworthy that macrocephaly is usually present from birth and persists into adulthood [DiLiberti, 1998].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Both patients came to our attention for clinical features suggestive of BRRS such as macrocephaly, developmental delay, and subcutaneous lipomatosis. Macrocephaly with normal ventricular size has been the most consistent finding in BRRS in several reviews [MorettiFerreira et al, 1989;Gorlin et al, 1992]. It is noteworthy that macrocephaly is usually present from birth and persists into adulthood [DiLiberti, 1998].…”
Section: Discussionmentioning
confidence: 89%
“…The molecular basis of CS in the remaining cases has yet to be determined. BRRS is a rare congenital syndrome characterized by macrocephaly, multiple hemangiomas, and lipomas (subcutaneous and/or visceral), gastrointestinal hamartomatous polyps, neurologic manifestations (autism or cognitive and motor developmental delay), and hyperpigmented macules on the skin of the shaft and glans penis [Gorlin et al, 1992]. Common features include hypotonia associated with a lipid storage myopathy [DiLiberti et al, 1984] and thyroid abnormalities such as Hashimoto's thyroiditis [Gorlin et al, 1992].…”
Section: Introductionmentioning
confidence: 99%
“…For purposes of clinical care, therefore, operational diagnostic criteria for CS have been developed which include macrocephaly as a major feature; 6 macrocephaly has also long been recognised as a hallmark characteristic of BRRS. 7,8 However, the true prevalence of macrocephaly is uncertain. A population-based study in Amsterdam including a review of the literature at that time cited a weighted prevalence of 21%, 2 whereas two other retrospective studies from tertiary referral centers found macrocephaly in 100% of patients studied.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Germline PTEN mutations are also associated with 65% of patients with Bannayan-Riley-Ravalcaba Syndrome, which is characterized by macrocephaly, lipomatosis, hemangiomatosis and speckled penis. 4,9 Somatic alterations in PTEN, whether by genetic or epigenetic mechanisms, play some role in the pathogenesis of a broad range of solid tumors, such as carcinomas of the breast, thyroid, endometrium and colon. 10 PTEN's protein product, PTEN, is a dual specificity phosphatase with both lipid and protein phosphatase activity.…”
mentioning
confidence: 99%